Neuroendocrine control of glucose homeostasis: integrative mechanisms from the hypothalamus to the brainstem - Gallardo, Nilda; Artigas-Jerónimo, Sara; Mazuecos, Lorena; Andrés, Antonio (Frontiers in Endocrinology, 2025)
Glucose is vital for brain physiological function, acting as the primary energy source that supports cognitive processes, neurotransmitter production, and overall health. The brain requires a constant supply of glucose, and the body has evolved protective mechanisms to maintain this supply during hypoglycemia. Increased appetite and food intake is a fundamental protective response. The precise network of brain regions, nerves, and connections responsible for initiating and coordinating these responses has not been fully identified or mapped. Neuroendocrine centers within the hypothalamus and brainstem monitor metabolic signals such as glucose, insulin, and leptin to regulate autonomic outflow, endocrine function, and behavior. Disruption of these central regulatory circuits contributes significantly to the pathogenesis of metabolic disorders, including obesity and type 2 diabetes mellitus (T2DM). Interestingly, incretin-based pharmacotherapies and bariatric surgery suppress food intake by acting on the brain, thereby enhancing the regulation of glucose homeostasis. This review summarizes current knowledge on the neural and hormonal pathways, including incretin signaling, involved in physiological glucose regulation, the mechanisms underlying their dysfunction in disease states, and the recent advances pointing to potential central targets for therapeutic intervention.